Analisis Representasi Rasisme pada Film Green Book (Pendekatan Semiotika John Fsike) - Faiza Andini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study analyzes the representation of racism in the film Green Book (2018) using John Fiske's semiotic approach. The movie tells the journey of Don Shirley, a famous black pianist, and his white personal driver, Tony, in the United States during the 1960s. Throughout the journey, Don Shirley often faces discriminatory treatment and harassment from white society, which is visualized through various social codes such as dialogue, facial expressions, and body gestures. Through the analysis of these social codes, this research reveals how the narrative and characters in the film construct and represent the issue of racism. The results show that Green Book not only displays racial conflict explicitly, but also conveys ideological messages about the importance of equality, tolerance and cooperation across races. This finding confirms that the film acts as a cultural mirror as well as a social critique of racial injustice that still occurs in society. Thus, this research is expected to broaden the understanding of the portrayal of racism in the media and contribute to the study of social representation in film.